Manajemen Risiko Sistem Informasi pada Perpustakaan Daerah Purwokerto - Ranggi Praharaningtyas Aji; Maruf Maftukhin; Rizky Bangkit Bachtiar (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The Regional Archives and Libraries Office of Banyumas Regency as a provider of archives and libraries is often demanded to provide fast, precise, and accurate information services. In order to fulfill this case, the Purwokerto Regional Library has implemented an information system on a daily basis. With the use of this information system, it will pose a threat and if it is not known precisely, it can cause harm to the Purwokerto Regional Library. The purpose of this research is to measure the risk in the information system in the Purwokerto Regional Library. For this reason, NIST SP 800-30 Rev 1 is used, which is a risk assessment model issued by the National Institute of Standards and Technology. The results of this study were in the form of an assessment of the 13 identified threats found in the Purwokerto regional library.